The spatial molecular pattern of integrin recognition sites and their immobilization to colloidal nanobeads determine α2β1 integrin-dependent platelet activation - Martins Lima, Augusto; Spatz, Joachim P. (Biomaterials, 2018)
Collagen, a strong platelet activator, is recognized by integrin α2β1 and GPVI. It induces aggregation, if added to suspended platelets, or platelet adhesion if immobilized to a surface. The recombinant non-prolylhydroxylated mini-collagen FC3 triple helix containing one α2β1 integrin binding site is a tool to specifically study how α2β1 integrin activates platelet. Whereas soluble FC3 monomers antagonistically block collagen-induced platelet activation, immobilization of several FC3 molecules to an interface or to colloidal nanobeads determines the agonistic action of FC3. Nanopatterning of FC3 reveals that intermolecular distances below 64nm between α2β1 integrin binding sites trigger signaling through dot-like clusters of α2β1 integrin, which are visible in high resolution microscopy with dSTORM. Upon signaling, these integrin clusters increase in numbers per platelet, but retain their individual size. Immobilization of several FC3 to 100nm-sized nanobeads identifies α2β1 integrin-triggered signaling in platelets to occur at a twentyfold slower rate than collagen, which activates platelet in a fast integrative signaling via different platelet receptors. As compared to collagen stimulation, FC3-nanobead-triggered signaling cause a significant stronger activation of the protein kinase BTK, a weak and dispensable activation of PDK1, as well as a distinct phosphorylation pattern of PDB/Akt.